Fabrication of Bacterial Cellulose-Curcumin Nanocomposite as a Novel Dressing for Partial Thickness Skin Burn - Sajjad, Wasim; He, Feng; Ullah, Muhammad Wajid; Ikram, Muhammad; Shah, Shahid Masood; Khan, Romana; Khan, Taous; Khalid, Ayesha; Yang, Guang; Wahid, Fazli (Frontiers in Bioengineering and Biotechnology, 2020)
The current study aimed to fabricate curcumin-loaded bacterial cellulose (BC-Cur) nanocomposite as a potential wound dressing for partial thickness burns by utilizing the therapeutic features of curcumin and unique structural, physico-chemical, and biological features of BC. Characterization analyses confirmed the successful impregnation of curcumin into the BC matrix. Biocompatibility studies showed the better attachment and proliferation of fibroblast cells on the BC-Cur nanocomposite. The antibacterial potential of curcumin was tested against Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa), Salmonella typhimurium (S. typhimurium), and Staphylococcus aureus (S. aureus). Wound healing analysis of partial-thickness burns in Balbc mice showed an accelerated wound closure up to 64.25% after 15 days in the BC-Cur nanocomposite treated group. Histological studies showed healthy granulation tissues, fine re-epithelialization, vascularization, and resurfacing of wound bed in the BC-Cur nanocomposite group. These results indicate that combining BC with curcumin significantly improved the healing pattern. Thus, it can be concluded that the fabricated biomaterial could provide a base for the development of promising alternatives for the conventional dressing system in treating burns.